2019
DOI: 10.1111/aas.13526
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐controlled ventilation improves gas exchange in lung‐healthy patients— a randomized interventional cross‐over study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 25 publications
6
23
2
Order By: Relevance
“…However, minimal and maximal airway pressure and tidal volume remained unchanged. Our results are consistent with and enlarge upon earlier findings on the implications of a linearized expiratory pressure decrease in lung-healthy patients, lung healthy pigs and a porcine lung-injury model [6][7][8][9].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, minimal and maximal airway pressure and tidal volume remained unchanged. Our results are consistent with and enlarge upon earlier findings on the implications of a linearized expiratory pressure decrease in lung-healthy patients, lung healthy pigs and a porcine lung-injury model [6][7][8][9].…”
Section: Discussionsupporting
confidence: 92%
“…We did not perform arterial blood gas analyses to examine the effects of FCV on gas exchange in our patients. In preclinical [17] and clinical studies [8], the controlled expiration improved oxygenation and CO 2 elimination. However, in contrast to other centers, placing an arterial line is not part of our standard treatment in this patient group.…”
Section: Limitations Of the Studymentioning
confidence: 98%
See 1 more Smart Citation
“…However, minimal and maximal airway pressure and tidal volume remained unchanged. Our results are consistent with and enlarge upon earlier findings on the implications of a linearized expiratory pressure decrease in lung-healthy patients, lung healthy pigs and a porcine lunginjury model [6][7][8][9].…”
Section: Discussionsupporting
confidence: 92%
“…We showed that compliance-guided pressure adjustment with FCV did not cause more regional overin ation of lung tissue when compared to evidence-based, low tidal volume PCV even though higher V T s were applied with FCV. Several studies report a signi cant improvement in ventilation e ciency and aeration of lung tissue when FCV is applied [12,13,14,15,16]; however, these studies did not use an individualized ventilation approach. Our study shows that normocapnia was maintained in individualized FCV despite a remarkable reduction of respiratory minute volume by 50% compared to PCV.…”
Section: Discussionmentioning
confidence: 99%